2018
DOI: 10.32582/aa.59.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between small pelagic purse seine fishery and its top predators

Abstract: Due to very good collaboration with one commercial purse seiner, using “Srdelara” and operating in fishing zone G, preliminary data concerning the interaction between small pelagic purse seine fishery and its predators were obtained. According to the notes taken by experience observer on-board in period from year 2013 to 2016, seems that tunas, dolphins and swordfish were the faithful companions of purse seiner fisherman with abundance of 68.6%, 22.0% and 9.4%, respectively. Although they were present all year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Off the eastern and southern coasts of the Adriatic, commercial purse seining is intensive (Lucchetti et al, 2018) but information on potential interactions with this fishery is scant, possibly because most purse seining happens at night. In the inshore waters off southern Croatia, Zorica et al (2018) conducted observations in 2013-2016 from a single purse seiner operating at night with fishing lights, and concluded that "dolphins" (most likely bottlenose dolphins) were present year-round, with a higher occurrence between July and October. On average, there were dolphins near the purse seiner 22% of the time.…”
Section: Diet and Interactions With Fishing Gearmentioning
confidence: 99%
See 1 more Smart Citation
“…Off the eastern and southern coasts of the Adriatic, commercial purse seining is intensive (Lucchetti et al, 2018) but information on potential interactions with this fishery is scant, possibly because most purse seining happens at night. In the inshore waters off southern Croatia, Zorica et al (2018) conducted observations in 2013-2016 from a single purse seiner operating at night with fishing lights, and concluded that "dolphins" (most likely bottlenose dolphins) were present year-round, with a higher occurrence between July and October. On average, there were dolphins near the purse seiner 22% of the time.…”
Section: Diet and Interactions With Fishing Gearmentioning
confidence: 99%
“…On average, there were dolphins near the purse seiner 22% of the time. The authors contended that dolphins "help rounding up the school of small pelagic fish as no decrease in catches due to its appearance were noted, actually higher catches were realised in their presence" (Zorica et al, 2018). In Montenegro, bottlenose dolphin interactions with fishing boats including purse seiners were reported by Rudd et al (2022), but no other information is available.…”
Section: Diet and Interactions With Fishing Gearmentioning
confidence: 99%